High-Throughput mRNA Sequencing Reveals Potential Therapeutic Targets of Febuxostat in Secondary Injury After Intracerebral Hemorrhage - Xueyan Wang; Chenyu Zhang; Chenyu Zhang; Yuwen Li; Yuwen Li; Ting Xu; Ting Xu; Jin Xiang; Yang Bai; Ying Zhang; Qi Wang; Tiejun Zhang; et al. (Frontiers Media S.A., 2022)
Febuxostat is a urate-lowering medication for the treatment of patients with gout. This study was performed to elucidate the effects and underlying mechanisms of febuxostat on neuronal injury induced by intracerebral hemorrhage (ICH) in mice. The results showed that the administration of febuxostat improved neurological severity scores and blood-brain barrier (BBB) permeability. Moreover, febuxostat attenuated neuronal cell death and cytokine levels compared with the ICH group. Next, we conducted a transcriptome analysis of the neuroprotective effects of febuxostat. The overlapping significant differentially expressed genes (DEGs) were identified. Gene ontology (GO) analysis revealed that the overlapping significant DEGs were most enriched in five items. The intersecting DEGs of the aforementioned five pathways were Wisp1, Wnt7b, Frzb, and Pitx2. In addition, GO terms and Kyoto Encyclopedia of Genes and Genomes (KEGG) pathways revealed that DEGs were mainly involved in the wnt signaling pathway. Furthermore, the expression of Wisp1 and Wnt7b in the perihematomal region at 72 h post-ICH was observed. The results showed that both Wisp1 and Wnt7b were increased in the ICH group and were decreased by the administration of febuxostat. Taken together, the study showed that febuxostat protected against secondary brain injury after ICH and the Wnt7b-Wisp1 pathway was closely related to neuroprotective effects.